Ethnicity-specific distribution of TRPM8 gene variants in Eurasian populations: signs of selection - T. A. Potapova; A. G. Romashchenko; N. S. Yudin; M. I. Voevoda (Вавиловский журнал генетики и селекции, 2020)
The TRPM8 gene encodes the ion channel, which is a cold receptor in afferent neurons of the mammalian somatosensory system. We studied the frequency of haplotype distribution from six SNPs in the TRPM8 gene in Eurasian human populations, including Russians, Kazakhs and Chukchi. Four of the six SNPs are located in exon 7 (rs13004520, rs28901637, rs11562975, rs17868387), rs7593557 is in exon 11. These exons encode parts of the N-terminus, which is necessary for channel functioning in the plasma membrane of neurons. The rs11563071 is in exon 23 encoding part of the C-terminus. The primary difference in population distribution of haplotypes determines the SNP from exon 11 which leads to Ser419Asn substitution in protein. The most pronounced differences in the patterns of diversity and frequencies of haplotypes were observed between Chukchi and Russians. The frequency of major H1 haplotype encompassing the 419Ser gene variant differs in examined populations; 0.738 (Russians), 0.507 (Kazakhs) and 0.337 (Chukchi), p < 0.001. The TRPM8 gene variants encoding 419Asn and carrying the minor alleles of rs28901637 (P249P) and rs11562975 (L250L) in exon 7 are characteristic of Asian populations. The frequency of all 419Asn variants in Chukchi is comparable to that in Africans, however, the minor allele frequencies of rs28901637, rs11562975 in Africans is low. Apparently in the process of human colonization of Eurasia, minor alleles of these SNPs diverged depending on rs7593557 structure in exon 11. We analyzed sequences of five TRPM8 mRNA isoforms extracted by researchers from different tissues. Sequence analysis demonstrates that they are transcribed from major H1 variant of the TRPM8 gene but contain different translation start codons, which are generated by alternative splicing from pro-mRNA.